Age, political knowledge and electoral turnout: a case study of Canada. Issue 1 (2nd January 2017) - Stockemer, Daniel; Rocher, Francois
Abstract : This article attempts to explain declining levels of voter turnout among young adults in terms of decreasing levels of political knowledge. Using data from a representative national survey of the Canadian electorate conducted in 2007, we find through descriptive and inferential statistics that younger individuals are more politically illiterate than older generations by a margin of 20–30 percentage points. We also detect that this generational political knowledge gap accounts for approximately half of the turnout gap that exists between voters in their early 20s and voters in their 50s. Our results further demonstrate that eliminating the knowledge gap would significantly increase turnout among young voters by 15 percentage points.